PENGARUH GERAK CHALLENGE TERHADAP MOTORIK KASAR ANAK USIA DINI BERBANTUAN TIKTOK - Morinda Sari; Dadan Suryana; Nurhafizah; Rismareni Pransiska (STKIP Subang, 2026)
This article is written based on research motivated by the low gross motor skills of young children, the limited variety of learning activities, and the frequent use of worksheets that are supposed to provide optimal stimulation. These conditions result in children's gross motor skills not developing to their full potential. To address this issue, Movement Challenge with the help of TikTok is introduced as a fun, varied activity that grabs children's attention and gives them the chance to move actively and skillfully. This study aims to find out the effect of TikTok-assisted Movement Challenge on the gross motor skills of 5-6 year old children in group B1 at Sabbihisma 4 Kindergarten in Padang. The method used is a quantitative approach with a Quasi-Experimental design (Nonequivalent Control Group Design), involving two groups: an experimental group that receives the Movement Challenge activity and a control group that follows conventional learning. The research sample consists of class B1 as the experimental class with 10 children and class B2 as the control class with 10 children, selected using purposive sampling. Data collection techniques include tests, observation, and documentation. Data analysis is carried out through normality test, homogeneity test, and Hypothesis testing was done using an Independent Sample t-test. The research results showed that the average gross motor skills score of children in the experimental class increased from 9.3 in the pre-test to 22 in the post-test. The hypothesis test results got a Sig. (2-tailed) value of 0.001 < 0.05, so it can be concluded that there is a significant effect of TikTok-Assisted Movement Challenge on the gross motor skills of 5-6-year-old children in group B1 at TK Sabbihisma 4, Padang City.